2008
DOI: 10.1016/j.athoracsur.2007.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Imaging as a Quality Assurance Tool for Evaluating Endoscopic Harvest of the Radial Artery

Abstract: Background-Concerns about intimal disruption and spasm have limited enthusiasm for endoscopic radial artery harvest (ERAH), although the risk of these problems after this procedure remains uncertain. Radial artery conduits were screened intraoperatively before and after ERAH vs open harvest using catheter-based high-resolution optical coherence tomogaraphy (OCT) imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The risk of potential graft injury caused by ERAH is debated, against the backdrop of endoscopic vein harvesting (EVH) results. Although, vasoreactivity and patency rate of harvested RA graft seem to be comparable, a higher incidence of intimal tears was displayed on optical coherence tomography imaging 25,28 . Analogously to EVH, from 2009 we have adopted some precautions in ERAH technique including routine low-dose pre-heparization, no port-seal and minimal CO 2 insufflation pressure, and use of the hemoseal system with minimal thermal spread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of potential graft injury caused by ERAH is debated, against the backdrop of endoscopic vein harvesting (EVH) results. Although, vasoreactivity and patency rate of harvested RA graft seem to be comparable, a higher incidence of intimal tears was displayed on optical coherence tomography imaging 25,28 . Analogously to EVH, from 2009 we have adopted some precautions in ERAH technique including routine low-dose pre-heparization, no port-seal and minimal CO 2 insufflation pressure, and use of the hemoseal system with minimal thermal spread.…”
Section: Discussionmentioning
confidence: 99%
“…Although, several harvesting systems are employing for ERAH, there are no data comparing the influence on bipolar electrocauthery, harmonic scalpel or direct current on the conduit quality used for branch division in each system. However, the issue of conduit quality harvested endoscopically needs to be appraised carefully in light of the results of optical coherence tomography imaging and sub-analysis of the PREVENTIV study 25,26 . Our results showed a significant learning curve of ERAH even with ample previous experience using endoscopic vein harvesting techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, some researchers demonstrated that sealed systems have a detrimental effect on RA integrity in terms of intimal disruption and potential ostial tears at the origin of side branches [12], whereas others observed a preserved vasoreactivity and endothelial integrity of RA conduits harvested with an endoscopic, nonsealed system [13] We, therefore, sought to investigate the impact of the endoscopic technique with a nonsealed system for RA procurement on clinical outcomes in the early postoperative period and at midterm (5-year) follow-up. To minimize the bias in the interpretation of the results, careful patient selection was performed: among other factors, the distribution of target vessels for the RA had to be similar among the two study populations.…”
Section: Commentmentioning
confidence: 99%
“…Furthermore, some authors reported that the use of a 'sealed' system may be associated with a higher degree of side branch injury and avulsion (especially for the radial artery), when the harvested conduits were analysed by means of optical coherence tomography [5].…”
Section: Surgical Techniquementioning
confidence: 99%